Is the Distribution of Inheritance in the Quran Final? An Epistemological Analysis of the Concept of Gender Justice in Fiqh Mawārīth - Abdelhadi Oussama; Majeed Elhassaneen; Emad Abbas Saeed; Ahmed Kathem Nasser; Hashim Manal Elsawy (Arba: Jurnal Studi Keislaman, 2026)
The debate regarding the finality of inheritance distribution in the Quran has emerged in contemporary Islamic jurisprudence discourse, particularly when confronted with demands for gender justice. Although inheritance verses are often understood as qatʻī (definite) provisions, few studies have systematically distinguished between the text’s normative finality and the epistemological dynamics of Islamic jurisprudence as a product of ijtihād. This study aims to analyze the epistemological status of inheritance verses by examining the concept of qatʻiyyat al-Dalālah (definite naṣṣ) in uṣūl al-Fiqh and evaluating the construction of gender justice in classical and contemporary mawārīṡ fiqh arguments. This study is qualitative with an epistemological-critical approach, using conceptual analysis and argumentative criticism of the istidlāl structure in uṣūl al-Fiqh literature and works of Islamic jurisprudence across schools of thought, as well as critical dialogue with current academic discourse on gender. The results of this study indicate that the finality of the inheritance verses lies in the normative authority of the text as a primary source, not in the overall construction of distribution built through the process of ijtihād. Analysis of the categories of qatʻī and ẓannī (presumption) indicates the existence of interpretive space in the rationalization of ʻillah, the determination of social context, and the formulation of distributive justice. Within this framework, gender justice is formulated as an internal epistemic principle that tests the coherence, consistency, and relevance of legal arguments without negating the authority of revelation. These findings offer a model of epistemological distinction between text and fiqh and emphasize the openness of the development of fiqh mawārīth methodologically and reflectively within the framework of Islamic legal epistemology.